Airway ciliated cells regenerated on collagen sponge implants acquire planar polarities towards nearby edges of implanted areas. (31st May 2021) - Nakamura, Ryosuke; Katsuno, Tatsuya; Tsuji, Takuya; Oyagi, Seiji; Kishimoto, Yo; Suehiro, Atsushi; Tateya, Ichiro; Omori, Koichi
Summary: Tissue‐engineered tracheae have been developed to replace defective tracheae. However, the direction of ciliated cells in the regenerated epithelium remains unclear. We investigated planar polarity formed in the regenerated airway epithelium after tracheal graft implantation. We partially resected the rat trachea and implanted a collagen scaffold. The direction of the basal foot was assessed by transmission electron microscopy. Immunofluorescence staining was performed to examine the biased distribution of Vangl1 and Frizzled6 proteins. The direction of mucociliary transport was analyzed by video microscopy. Our results showed that the basal feet of cilia in the proximal and distal regions of the implanted areas were respectively oriented toward the proximal and distal directions. The biased distribution of Vangl1 and Frizzled6, and the directions of mucociliary transport showed that planar polarities formed in the regenerated epithelium were oriented toward the proximal, distal, left, and right directions in the proximal, distal, left, and right regions of the implanted area. These polarities persisted until nine months after implantation. Hence, the results suggest that planar polarities formed in epithelia regenerated on tracheal grafts are directed toward the nearby edges of implanted areas and are preserved for a prolonged period. The polarities can, at least partially, contribute to clearing external materials from the implanted areas by transporting them to a normal region.